EFL Teachers’ Technological Pedagogical Content Knowledge (TPACK): Urban and Suburban Schools in East Java - Musyarrofah, Hamdatul; Setiawan, Slamet; Munir, Ahmad (Department of English Language Education, UIN Sunan Ampel Surabaya, 2023)
The advancement of technology encourages teachers to not only have great pedagogical and content knowledge but also technological knowledge to improve their teaching. In this study, the researcher aimed to measure the both urban and suburban teachers’ TPACK level, as well as the teaching activities they implemented. The researcher distributed questionnaire and conducted interview to collect the data. The findings indicated that there was not significantly difference between urban and suburban teachers. From 4-point scale, the total average scores were 3.3 for suburban teachers and 3.5 for urban teachers. The lowest score was 2.75 gained by suburban teachers in three items including monitoring their own writing for accuracy, monitoring their own speech for accuracy, and selecting authentic English language resources to suit students’ needs. They provided different kinds of activities namely reading kinds of texts and stories followed by exercises for example fill in the blanks, and question and answer sessions, listening to audio, song or video followed by retelling or doing exercises, and writing stories. All in all, teachers’ TPACK were already great but in several points they need to improve so that the teaching-learning process offer equal aspects.